Effectiveness of using a slider-crank mechanism for waffle background milling - I. N. Drozdov; A. Yu. Popov (Архитектура, строительство, транспорт)
The paper presents the design of an experimental cutting tool feed drive based on a slider-crank mechanism. A feature of the technology of milling a regular waffle background pattern is the need for regular repetition of cells, usually rectangular shape. This requires the development of a tool feed mechanism that provides а high processing speed and a significant reduction in cutting forces to prevent deformation of the cell shape. The drive design presented in the work provides feed rate up to 43 m/min with cutting speed up to 942 m/min. This eliminates the exit of the mechanism out of the cell dimensions, as well as provides a significant reduction of cutting forces up to 10 N and removes the problem of using coolant (dry machining). This is a feature of the high-speed milling mode, when the feed rate and cutting speed are significantly higher than traditional ones, and the cutting depth does not exceed 1 mm. The productivity of this milling process is much higher than traditional milling modes and, in addition, it causes less heating of the part, as almost all the heat escapes with the chips. The practical significance of the development is the increase of productivity of the equipment for waffle background milling in fuel tanks from aluminium alloys due to the application of the high-speed drive based on the slider-crank mechanism. The authors offered to mount it instead of the standard spindle on large-sized milling gantry-type machines. This makes it possible to use the high-speed milling modes at cutting forces of several newtons for reducing the weight of the power and moving parts of the drive and increasing the feed rate.